2008
DOI: 10.1364/oe.16.018371
|View full text |Cite
|
Sign up to set email alerts
|

Imaging with extended focal depth by means of the refractive light sword optical element

Abstract: The paper presents first experiments with a refractive light sword optical element (LSOE). A refractive version of the LSOE was prepared in photoresist by gray scale photolithography. Then we examined chromatic aberrations of the produced element and compared them with those corresponding to two different lenses. For this purpose we performed two experiments, the first one where white light illumination was used and the latter one by the help of monochromatic illumination with three different wavelengths. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…23 The optical properties of the LSL and its imaging with extended depth of field have been widely studied numerically and experimentally. [20][21][22][23][24]26,27 These investigations confirmed that the images formed by the LSL have acceptable resolution and contrast. Therefore, lenses with angular modulation of optical power such as the LSL can be useful for imaging with extended depth of field.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…23 The optical properties of the LSL and its imaging with extended depth of field have been widely studied numerically and experimentally. [20][21][22][23][24]26,27 These investigations confirmed that the images formed by the LSL have acceptable resolution and contrast. Therefore, lenses with angular modulation of optical power such as the LSL can be useful for imaging with extended depth of field.…”
supporting
confidence: 58%
“…This way, the refractive LSL can be used for imaging with extended depth of field in polychromatic light. 21 Moreover, computational results demonstrated the uniformity of Strehl's ratio of the LSL, which is almost constant along the entire length of the focal segment. 26 The ability of the LSL to correct presbyopia was studied in a model of the presbyopic human eye illuminated by white light.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…A new approach to extending DOF in contact lenses is offered by what has been called the ‘light sword optical element’ . This can be regarded as a lens in which the power varies with the orientation of the semi‐diameter, so that successive lens sectors show a gradually changing power.…”
Section: Contact Lensesmentioning
confidence: 99%
“…This can be regarded as a lens in which the power varies with the orientation of the semi‐diameter, so that successive lens sectors show a gradually changing power. It is claimed that the DOF as judged by preservation of the Strehl ratio or visual tests is substantially enhanced over a range of pupil diameters. As yet development of such lenses is at an early stage.…”
Section: Contact Lensesmentioning
confidence: 99%